The Politics of Big Data Assemblages - Aragona, Biagio; Felaco, Cristiano; Marino, Marina (PARTECIPAZIONE E CONFLITTO, 2018)
One way to study the politics of big data is the inspection of their assemblages. By opening up the “black boxes” of data assemblages, it is possible to reconstruct the choices, compromises, conflicts and agree-ments that contributed to the construction of a given datum. Leaning on in-depth interviews and focus groups with experts and specialists who work within three European data centers, we unveil the interde-pendence between social and technical aspects and between a series of internal and external actors, which all contribute to the data assemblage. Results show that communities of experts, technologies, stakeholders and end-users are entwined components that interact amongst them in a contingent and complex web of negotiations and constraints and frame what is possible, desirable and expected by data.